2017
DOI: 10.1111/ipd.12334
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effects of supervised toothbrushing on caries incidence in children and adolescents

Abstract: Background The anticaries effect of supervised toothbrushing, irrespective of the effect of fluoride toothpaste, has not been clearly determined yet. Aim To assess the effects of supervised toothbrushing on caries incidence in children and adolescents. Design A systematic review of controlled trials was performed (CRD42014013879). Electronic and hand searches retrieved 2046 records, 112 of which were read in full and independently assessed by two reviewers, who collected data regarding characteristics of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
1
23
0
10
Order By: Relevance
“…Many authors have shown that plaque accumulation is the primary cause of marginal periodontal inflammation [18][19][20][21]. Toothbrushing frequency has also a correlation with Decayed Missed Filled Tooth Index (DMFT), resulting in a lower susceptibility to dental caries development [22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have shown that plaque accumulation is the primary cause of marginal periodontal inflammation [18][19][20][21]. Toothbrushing frequency has also a correlation with Decayed Missed Filled Tooth Index (DMFT), resulting in a lower susceptibility to dental caries development [22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, one study showed a dose-response relationship between the prevalence of caries and brushing frequency in children [55]. Other studies which have looked at the overall effect of school-based tooth-bushing programs on caries experience have shown mixed results [57,58]. Associations between dental caries and other oral health promotion factors were not evident in our study but could be due to the use of self-reported data which has its limitations (see Section 4.4).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Entretanto, não há evidências que métodos que diminuiriam a transmissibilidade de micro-organismos orais entre cuidadores e crianças, sejam efetivos no controle da cárie em crianças. 18 A internet pode ser um instrumento poderoso para divulgação dessas recomendações.…”
Section: Discussionunclassified